Morphology and Microstructure of As-Synthesized Anodic TiO2 Nanotube Arrays - Song Xueping; Sun Zhaoqi; Cao Chunbin; Zhang Guoshun (Nanoscale Research Letters, 2011)
Abstract The as-grown structure of electrochemically synthesized titania nanotube arrays is investigated by scanning electron microscope (SEM) in combination with transmission electron microscope (TEM) as well as X-ray diffraction (XRD). The analysis reveals a preferred growth direction of the nanotubes relative to the substrate surface and the well control on the nanotube arrays morphology. The crystal structure of the anatase phase is detected and exists in the tube walls without any thermal treatment, which makes it possible to realize the application of as-formed TiO2 nanotubes avoiding the degradation of the nanotube structures when sintering. In addition, a new growth, layered model of the anodic TiO2 nanotubes is presented to obtain further understanding of the growth mechanism.